2006
DOI: 10.1017/s0266078406004020
|View full text |Cite
|
Sign up to set email alerts
|

World Englishes and the American tongue

Abstract: Are the other varieties of English under threat from the United States? This paper reviews the place of the United States of America (her English and culture) in the contemporary world, especially with regard to the spread and use of the English language. World War II and its aftermath raised America to the height of political, economic, commercial, technological strength which saw the transformation of English from being a reserve of the British Isles and their queen, to a code of international linguistic tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 2 publications
0
6
0
1
Order By: Relevance
“…For increasing numbers of learners, the mastery of Standard English in BrE trappings is not as enticing today as it was in the past. In fact, there is mounting evidence that AmE is now challenging BrE as the most preferred target variety (see Anchimbe, 2006). Mollin is apparently not aware of this shift in attitude.…”
Section: Variety Statusmentioning
confidence: 99%
“…For increasing numbers of learners, the mastery of Standard English in BrE trappings is not as enticing today as it was in the past. In fact, there is mounting evidence that AmE is now challenging BrE as the most preferred target variety (see Anchimbe, 2006). Mollin is apparently not aware of this shift in attitude.…”
Section: Variety Statusmentioning
confidence: 99%
“…Our findings demonstrated that 56% of the movies were from inner circle countries; however, the distribution of the movies was not even among inner circle countries, as American movies constituted 41% of all the movies: larger than Turkish movies’ share, and twice the percentages of all the other inner circle country movies combined (see Anchimbe [2006] for a discussion of how American variety of English affects other inner circle varieties). This finding is not surprising considering the fact that the market share of American movies compared to those of other countries is high and increasing around the world.…”
Section: Resultsmentioning
confidence: 76%
“…That claim seems theoretical since in practice, students, teachers and media men comfortably blend the two varieties. Following that, the researcher proposes that it is time the country adopts the use of the two varieties because undoubtedly, the two have gained the status of world language to the extent that AmE is overriding the other (Anchimbe, 2006). The position of this paper appears very different in a sense that many scholars have insisted on the continuity of the "norm"…”
Section: Resultsmentioning
confidence: 94%
“…Gongalves' et al 2017is unique compared to the works discussed earlier because the latter is a corpus-based study and also considers the language of both written form (books) and that of social between Gongalves' et al and Anchimbe (2006) is that both investigate which of the two major varieties of English is gaining prominence as regards the people's choice of vocabulary and spelling of a particular variety. Interestingly, all the others referred to in this study concentrate on the two aspects: spelling and orthography.…”
Section: The Place Of English In Ghanamentioning
confidence: 99%
See 1 more Smart Citation